Early effect of thrombolysis on structural brain network organisation after anterior‐circulation stroke in the randomized WAKE‐UP trial. Issue 16 (14th September 2022) - Schlemm, Eckhard; Jensen, Märit; Kuceyeski, Amy; Jamison, Keith; Ingwersen, Thies; Mayer, Carola; Königsberg, Alina; Boutitie, Florent; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Fiehler, Jens; et al.
Abstract: The symptoms of acute ischemic stroke can be attributed to disruption of the brain network architecture. Systemic thrombolysis is an effective treatment that preserves structural connectivity in the first days after the event. Its effect on the evolution of global network organisation is, however, not well understood. We present a secondary analysis of 269 patients from the randomized WAKE‐UP trial, comparing 127 imaging‐selected patients treated with alteplase with 142 controls who received placebo. We used indirect network mapping to quantify the impact of ischemic lesions on structural brain network organisation in terms of both global parameters of segregation and integration, and local disruption of individual connections. Network damage was estimated before randomization and again 22 to 36 h after administration of either alteplase or placebo. Evolution of structural network organisation was characterised by a loss in integration and gain in segregation, and this trajectory was attenuated by the administration of alteplase. Preserved brain network organization was associated with excellent functional outcome. Furthermore, the protective effect of alteplase was spatio‐topologically nonuniform, concentrating on a subnetwork of high centrality supported in the salvageable white matter surrounding the ischemic cores. This interplay between the location of the lesion, the pathophysiology of the ischemic penumbra, and the spatial embedding of the brain network explains the observed potential of thrombolysis to attenuate topological network damage early after stroke. Our findings might, in the future, lead to new brain network‐informed imaging biomarkers and improved prognostication in ischemic stroke. Abstract : We present a secondary analysis of 269 patients from the randomized WAKE‐UP trial. Using indirect network mapping to quantify the impact of ischemic lesions on structural brain network organisation we show that evolution of structural network organisation was characterised by a loss in integration and gain in segregation, and that this trajectory was attenuated by the administration of alteplase. The protective effect of alteplase was spatio‐topologically non‐uniform, concentrating on a subnetwork of high centrality supported in the salvageable white matter surrounding the ischemic cores.